IMPLEMENTATION OF MUHADHOROH ACTIVITIES IN IMPROVING STUDENTS' PUBLIC SPEAKING AT THE ADLANIYAH MODERN ISLAMIC BOARDING SCHOOL IN WEST PASAMAN - Septiawan, Harzen; Aini, Sukma (Mandeh : Jurnal Pendidikan Islam, 2025)
This research is motivated by the implementation of muhadhoroh activities in improving public speaking of students. Muhadhoroh activities are mandatory extracurricular activities that must be followed by all students of the Modern Adlaniyah Islamic Boarding School. In the implementation of this muhadhoroh activity, of course, there are obstacles and constraints in its implementation. Especially for students who are an important aspect for the Islamic Boarding School, they must have a series of problems in implementing this muhadhoroh activity. The formulation of the problem in this study is how the implementation of muhadhoroh activities in improving public speaking of students at the Modern Adlaniyah Islamic Boarding School, West Pasaman? Which is limited to muhadhoroh activities, muhadhoroh activity programs, implementation of muhadhoroh activities, driving and inhibiting factors of muhadhoroh activities at the Modern Adlaniyah Islamic Boarding School, West Pasaman. This study uses a qualitative descriptive approach to collect data from various respondents who participated in this study such as, the head of student care, student mentors, and students of the Modern Adlaniyah Islamic Boarding School, West Pasaman. This data was collected through observation, in-depth interviews, and document analysis with a focus on the implementation of muhadhoroh activities in improving public speaking of students at the Adlaniyah Modern Islamic Boarding School, West Pasaman. The results of this study indicate that the implementation of muhadhoroh activities at the Adlaniyah Modern Islamic Boarding School, West Pasaman has been carried out, although there are still obstacles in the implementation of muhadhoroh activities, both in terms of student abilities, facilities and learning resources, inadequate facilities and infrastructure.